National debt return 1965 - 68 - United Kingdom Treasury (Office Her Majesty's Stationery Office, 1967)
This returns gives particulars of changes in the national debt and of the issues made for the service debt in the year 1965-68. Additional information regarding the distribution of the National debt may be found in the annual abstract of statistics.
nmn, 10/05/19
Loans
Keywords: Debt Management; Debt return; United Kingdom